Effectiveness of Community Health Financing in Meeting the Cost of Illness - Preker, Alexander S. (World Bank, Washington, DC, 2013)
How to finance and provide health care for the more than 1.3 billion rural poor and informal sector workers in low- and middle-income countries is one of the greatest challenges facing the international development community. This article presents the main findings from an extensive survey of the literature of community financing arrangements, and selected experiences from the Asia and Africa regions. Most community financing schemes have evolved in the context of severe economic constraints, political instability, and lack of good governance. Micro-level household data analysis indicates that community financing improves access by rural and informal sector workers to needed heath care and provides them with some financial protection against the cost of illness. Macro-level cross-country analysis gives empirical support to the hypothesis that risk-sharing in health financing matters in terms of its impact on both the level and distribution of health, financial fairness and responsiveness indicators. The background research done for this article points to five key policies available to governments to improve the effectiveness and sustainability of existing community financing schemes. This includes: (a) increased and well-targeted subsidies to pay for the premiums of low-income populations; (b) insurance to protect against expenditure fluctuations and re-insurance to enlarge the effective size of small risk pools; (c) effective prevention and case management techniques to limit expenditure fluctuations; (d) technical support to strengthen the management capacity of local schemes; and (e) establishment and strengthening of links with the formal financing and provider networks.